The Impact of National Culture on Strategic IT Alignment: A Multiple-case Study of Subsidiaries of Multinational Corporations. Issue 4 (2nd October 2022) - Adaba, Godfried B.; Wilson, David W.; Sims, Julian
ABSTRACT: Through a multiple-case study of three subsidiaries of multinational corporations (MNCs), we examined the impact of national culture on strategic information technology (IT) alignment. We found that the headquarters and subsidiary host national cultures affect alignment indirectly, through variables in the organizational context, including intercultural communications, IT governance, management style, differences in work values and practices, and cultural conflict and mistrust. Based on the findings, we propose a model of national culture and alignment.